2019
DOI: 10.1029/2019jd030524
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Impact on Water and Energy Cycle During Dry Years Over the United States Using Convection‐Permitting WRF and a Dynamical Recycling Model

Abstract: An irrigation scheme is implemented in the Weather Research and Forecasting (WRF) model to investigate irrigation impacts over the Continental U.S. (CONUS). Four major irrigated regions and two downwind regions were chosen to understand irrigation impacts over different climate regimes with a focus on irrigation‐induced changes on the water and energy cycles. The Dynamic Recycling Model (DRM) is employed to quantify precipitation induced by irrigation and the precipitation recycling ratios over each irrigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 60 publications
2
44
0
1
Order By: Relevance
“…For example, an underestimation in evaporative fraction (EF, defined as the ratio of LH to the sum of LH and SH) has been attributed as the dominant source of error in models with a large warming bias. Handling of anthropogenic impacts (or lack thereof), such as neglecting irrigation in the LSMs, has also been attributed to the warming bias (Pei et al., 2016; Qian et al., 2020; Z. Yang et al., 2019). Here, we show that increased LH and decreased SH occur when lateral flow is considered, suggesting that lateral flow might also play an important role in alleviating the warming bias over the SGP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an underestimation in evaporative fraction (EF, defined as the ratio of LH to the sum of LH and SH) has been attributed as the dominant source of error in models with a large warming bias. Handling of anthropogenic impacts (or lack thereof), such as neglecting irrigation in the LSMs, has also been attributed to the warming bias (Pei et al., 2016; Qian et al., 2020; Z. Yang et al., 2019). Here, we show that increased LH and decreased SH occur when lateral flow is considered, suggesting that lateral flow might also play an important role in alleviating the warming bias over the SGP.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation water is added as precipitation to mimic the sprinkler system. Further details on the irrigation scheme can be obtained from the previous studies (Ozdogan et al., 2010; Qian et al., 2013; Yang et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Irrigation has immensely contributed to ensuring the food security of about 1.4 billion people in India. A massive expansion of 40 million hectares (mha) in the net irrigated area occurred between 1950 and 2008 (Ambika et al., 2016), which had profound impacts on groundwater abstraction, construction of reservoirs, and water and energy cycles (Asoka et al., 2017; Boucher et al., 2004; Shah et al., 2019; Yang et al., 2019). Previous studies identified a substantial imprint of irrigation on local climate, land surface temperature (LST), and atmospheric aridity (Ambika & Mishra, 2019; Shah et al., 2019; Thiery et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Leng et al (2013) reported that the irrigation amount simulated by CLM4 can be improved by tuning model parameters (e.g., weighted factor related to target soil moisture) and implementing a more accurate representation of the spatial distribution and intensity of irrigated areas. Additional water from irrigation can lead to increases in the soil water content and lower surface temperature and sensible/latent heat fluxes, with the potential to change boundary layer dynamics and regional scale precipitation patterns (Devanand et al, 2019;Qian et al, 2013;Thiery et al, 2017;Yang et al, 2019). It is therefore imperative to improve the simulation of irrigation which can significantly affect the simulated effects of irrigation on land-atmosphere exchange of water, carbon, and energy fluxes as well as regional/local climates.…”
Section: Irrigationmentioning
confidence: 99%